The Influence Of Live Commerce On Tiktok Platform And Discount Vouchers On Consumer Purchasing Decisions For Cosmetic Products In Palopo City - Nurjannah; Munawir; Muhammad Isnaini Faizal; Muh. Haekal Yunus (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to analyze the influence of Live Commerce on the TikTok platform and Discount Vouchers on Consumer Purchasing Decisions for Cosmetic Products (Study on Female Students of the Faculty of Economics and Business Unanda Class of 2023). Female students tend to be more interested in making purchases when exposed to live promotional broadcasts of products on TikTok accompanied by discount offers. This study uses a quantitative approach with a survey method, involving 73 student respondents selected through purposive sampling techniques. Data was collected using structured questionnaires and analyzed using multiple linear regression. The results show that live commerce on the TikTok platform has a significant positive influence on consumer purchasing decisions, meaning that the more attractive and interactive the live commerce content displayed on the TikTok platform, the greater the likelihood of consumers to make purchasing decisions for the cosmetic products offered. Conversely, discount vouchers have a significant negative influence, meaning that the use of discount vouchers does not always encourage purchases, and in this context can actually reduce consumer trust or urgency to immediately buy cosmetic products. This study provides implications for female students to be wiser in responding to digital marketing strategies such as live commerce and discount vouchers when purchasing cosmetic products